Magnetic Nanocatalysis. - Babu, J. Nagendra; Banerjee, Bubun; Brar, Ravinderdeep Singh; Dandia, Anshu; Ghosh, Pranab; Gonzalez, Lucy T.; González, Cesar Maximo Oliva; Hussain, Khadim; Jonnalagadda, Sreekantha B.; Kerru, Nagaraju; Kharisov, Boris I.; Kharissova, Oxana V.; et al. (Magnetic Nanocatalysis, 2022)
Magnetic nanocatalysts are garnering attention for development of greener catalytic processes due to their ease of recovery from a reaction medium. This book delves into a variety of magnetic nanocatalysts, their use in the industrial context, and recyclability. Topics covered include wastewater treatment, drug delivery, and industrial catalysis; another available volume focuses on the use of magnetic nanocatalysts in synthetic appliances and transformations.